Teledermatology in the diagnosis and treatment of sexually transmitted infections: a narrative review - Woźna, Julia; Stępka, Jan; Bałoniak, Andrzej; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2024)
Teledermatology is a dynamically developing field of medicine with the potential to significantly impact the future functioning of the healthcare system, including the prevention, diagnostics, and treatment of sexually transmitted infections (STIs). While its implementation has resolved numerous issues associated with the traditional patient management model for STIs, the risk associated with handling sensitive patient data in a virtual space must not be overlooked. This article presents a literature review regarding the application of teledermatology in the diagnostics and treatment of STIs, with a particular focus on addressing relevant problems, potential obstacles, and examining the impact of the COVID-19 global epidemic on the development of this field.